2018
DOI: 10.1037/rep0000206
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, psychosocial, and health- and disability-related factors associated with psychological distress among people with physical disabilities.

Abstract: PWPD who are unemployed, less educated, with a shorter duration of disability and lower self-rated health, as well as those who feel more discriminated against and less social support, are more likely to experience higher levels of psychological distress. Therefore, it is important to raise PWPD's awareness of their rights and of the social possibilities and services available to them, to provide them with mental help, to engage in extensive social activities aimed at providing resources to PWPD, and to act to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Our results extend the findings of an earlier study linking stigma and depression in those with intellectual disability,17 by establishing this relationship in a sample with a broader range of disability. In keeping with previous studies, we observed greater psychological distress18–20 and poorer life satisfaction21–23 27 in those who reported disability discrimination. Our study adds to this existing evidence by demonstrating this link in a UK-based sample for the first time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results extend the findings of an earlier study linking stigma and depression in those with intellectual disability,17 by establishing this relationship in a sample with a broader range of disability. In keeping with previous studies, we observed greater psychological distress18–20 and poorer life satisfaction21–23 27 in those who reported disability discrimination. Our study adds to this existing evidence by demonstrating this link in a UK-based sample for the first time.…”
Section: Discussionsupporting
confidence: 91%
“…This association was similarly observed in a Swedish general population survey 20. Research has also linked perceived disability discrimination with lower life satisfaction in Canadian adolescents,21 Korean women with severe disabilities22 and Israeli nationals with physical disabilities 23. Perceived disability discrimination has been associated with poorer self-rated health cross-sectionally in four studies19 24–26 including a general population analysis of 52 458 individuals, from the European Social Survey 25…”
Section: Introductionmentioning
confidence: 63%
“…Except for the impact of being physically inactive, 20 which is a main risk factor for hypertension itself, physically disabled people are more vulnerable against psychological stress and discrimination, especially for those with spinal cord injury. 21 A previous study has suggested that physically disabled people may receive less benefits from the rehabilitation and healthcare services. 3 This may also contribute to a higher risk of hypertension among people with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This result is contrary to the negative influences on mental health identified in other literature: unemployment, low education level, a short duration of disability, low self-rated health and low levels of social support. 32 Perceived disability-related discrimination is associated with depression, while poor self-rated health and psychological distress are linked with poorer well-being. 33 The low vitality and high psychological distress levels of those living in residential homes are alarming, and more research on this issue has to be conducted.…”
Section: Discussionmentioning
confidence: 99%